LOST IN IDENTITY: A CASE STUDY OF CHIMAMANDA NGOZI ADICHIE’S SELECTED WORKS - SKRYPNIK , Iryna (Accents and Paradoxes of Modern Philology, 2021)
The article addresses the phenomenon of identity as it is described in modern multicultural literature and analyzes language means applied to actualize the basics of the notion of identity – opposition we-they. The phenomenon of identity, the spotlight of different scientific works due to its immense complexity and multifaceted nature, is of special interest for linguistic studies due to the unique ability of literary texts to reflect the reality and the power of language means to convey certain ideas and messages. The sense of belonging which is as essential for human beings as any other, is strictly determined by the opposition we-they. For the purpose of more profound understanding of this dyad that seems to govern and regulate personal and social interactions between people a number of approaches suggested by different scientists – sociologists, philosophers – have been examined. It seems that the presence of the “Other” predisposes a person’s existence and self-realization as it would be probably impossible to define oneself without recognition from the “Other”. The availability of the “Other” as the required element of our existence, the way we see it, determines the outcome of the interaction at any level. The boundaries that are set by the opposition “we-they” mean striving for recognition. The figure of the “Other” regarded as the enemy is triggered off by a wide range of conceptual metaphors (the metaphor of roots, of mirror, of haziness etc.) verbalized by various language means. Language itself is seen as one of the main means and a powerful tool of setting boundaries and defining oneself and has its specific role in the texts analyzed.